Eight Keys to an Extraordinary Board-Superintendent Partnership - Eadie, Doug (Rowman & Littlefield Publishers, 2003)
This book draws on author Doug Eadie's work with hundreds of boards to provide detailed, hands-on guidance for building and managing a board-superintendent partnership that is close, positive, productive, and enduring. Eadie describes how the superintendent can wear the "chief partnership officer" hat while leading and managing a board-superintendent partnership program. Special attention is paid to such critical partnership building tools such as: · Empowering the board · Building board member ownership of their governing work · Making governing work easier and more fun · Involving senior administrators in providing executive support to the board For superintendents, school board members, and school system senior administrators.